Diet quality and urbanization in Mozambique - Smart, Jenny; Tschirley, David; Smart, Francis (SAGE Publications, 2020)
Robust income growth combined with the highest urban population growth in the world is driving rapid changes in the food system of sub-Saharan Africa. Demand is increasing for higher quality as well as more processed foods. Countries are increasingly experiencing a double burden of over and under nutrition as the overweight and obesity epidemic spreads. In this context, we seek to understand the key drivers and likely evolution of diet quality in Mozambique, in both its positive and negative dimensions, while specifically examining the role of farm ownership among increasingly urban populations. We use national household expenditure survey data and a set of ordinary least square and analysis of variance regressions to observe patterns of current diet quality across city size categories, household income, household education, and other demographic variables. We then anticipate the likely directions of change in diet quality over these same dimensions based on expected income growth and expenditure elasticities developed for several alternative nutrients. We find that growing incomes and the consumption of processed foods are associated with a worsening of negative factors in the diet. Furthermore, urbanization, controlling for income, is associated more strongly with a worsening of negative factors than with an improvement in positive factors in the diet. The effect on diet quality of farm ownership, however, is positive and significant, primarily driven by these households purchasing fewer unhealthy foods. African cities need to consider what mix of policies will counteract the negative effects of continued urbanization and rising incomes on diets.